2022
DOI: 10.3390/healthcare10050799
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Perceived Health System Responsiveness of the Epilepsy Management Project in Rural China during the Period of COVID-19

Abstract: Health system responsiveness (HSR) measures the experience of health-system users in terms of the non-clinical domains of the health system, which has been regarded as the three major goals of health performance evaluation. Good HSR may promote the use of health services and ultimately the health of patients. However, the HSR has not been measured as the main goal of the Epilepsy Management Project (EMP) in rural China. This study aims to evaluate the levels and distributions of the patient-perceived HSR of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Subsequently, upholding a sense of responsiveness helps customers build trust and good relationships with service providers, which are one of the best ways to understand customers' problems and ensure timely availability of health services in a convenient manner. These findings concur with Kapologwe et al (2020) and Qin et al (2022) findings, which suggest that health service facilities with responsive service providers who are willing and able to respond to customers' queries on time stand a high chance of improving health service delivery. Table 3.…”
Section: Structural Model and Testing Of Hypothesessupporting
confidence: 83%
See 2 more Smart Citations
“…Subsequently, upholding a sense of responsiveness helps customers build trust and good relationships with service providers, which are one of the best ways to understand customers' problems and ensure timely availability of health services in a convenient manner. These findings concur with Kapologwe et al (2020) and Qin et al (2022) findings, which suggest that health service facilities with responsive service providers who are willing and able to respond to customers' queries on time stand a high chance of improving health service delivery. Table 3.…”
Section: Structural Model and Testing Of Hypothesessupporting
confidence: 83%
“…According to Mirzoev and Kane (2017), responsiveness encompasses service providers' readiness and willingness to provide prompt service to the target customers at any time without inducements. Consequently, the literature acknowledges a positive and significant relationship between responsiveness and health service delivery (Kapologwe et al, 2020;Qin et al, 2022;Malakoane et al, 2020). Service providers' responsiveness strongly influences the level of service quality.…”
Section: Literature Review 21 the Institutional Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected using the WHO questionnaire on responsiveness as well as a checklist on demographic information. The validity and reliability of this questionnaire are evaluated in Iran[ 14 ] in several studies conducted on various groups of patients. For outpatients, it contains seven domains of prompt attention (five items), dignity (four items), communication (four items), autonomy (three items), confidentiality (three items), choice of provider (three items), and basic amenities (three items).…”
Section: Methodsmentioning
confidence: 99%
“…The result of this study showed that the HSR was fairly good. [ 14 ] Despite the importance of research and documentation on the responsiveness of health services, to our knowledge, this is the first study conducted to investigate HSR after the announcement of the Covid epidemic in Iran.…”
Section: Introductionmentioning
confidence: 99%